FROM FAIRY TALES TO ACTION ADVENTURE MOVIE: THE MAINTENANCE OF WOMEN AS VICTIM OF VIOLENCE IN THE MOVIE SNOW WHITE AND THE HUNTSMAN (2012) - Restu Dedy Hendriyanto; Yusuf Kurniawan (Jurnal Penelitian Humaniora, 2020)
Gender representation is one of the most prominent subjects of discussion in American society. Fairy tales as one of the first cultural products consumed by the American society are a medium with an influential presence in the issue. They provide gender representations and convey the idea of masculine and feminine- myths of how to be men and women. However, in 20th century, many movies are changing the perspective by presenting women and action and break the traditional myth. In the same year, a movie entitled Snow White and the Huntsman appears as the remake of the written fairy tale Snow White in the form of an action-adventure movie. To move the discussion further, this research examines how the idea of women as victims of violence in the movie is maintained. A number of disciplines in the forms of theory and approach are used to analyze the data. It also applies gender theories and Barthes's semiotic theory in answering the research question. As a result, it is found that the character Snow White and a number of other women characters still become victims of violence. The representations are also still associated with the traditional ideas of women.